2020
DOI: 10.1093/cercor/bhaa354
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2R is Required for Hippocampal-dependent Memory and Plasticity at the CA3-CA1 Synapse

Abstract: Dopamine receptors play an important role in motivational, emotional, and motor responses. In addition, growing evidence suggests a key role of hippocampal dopamine receptors in learning and memory. It is well known that associative learning and synaptic plasticity of CA3-CA1 requires the dopamine D1 receptor (D1R). However, the specific role of the dopamine D2 receptor (D2R) on memory-related neuroplasticity processes is still undefined. Here, by using two models of D2R loss, D2R knockout mice (Drd2−/−) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 106 publications
1
24
0
Order By: Relevance
“…Our results in the episodic-like task and the cumulative semantic-like paradigm both showed that the rats performed worse in recognizing novel features of the objects in the presence of the D2R antagonist, compared to controls, during the final test sessions. These findings in rats align with reports from behavioral studies in mice in which D2R were either knocked-out or silenced specifically in the CA1 region, which demonstrated that spatial working memory (Glickstein et al, 2002), spatial and recognition learning and memory (Rocchetti et al, 2015), reversal learning and even associative learning, such as in trace eyeblink conditioning (Espadas et al, 2021) are all impaired when D2R function is disrupted. Others have reported that D2R-antagonism can affect movement initiation and execution (Amalric et al, 1993;Hauber, 1996;Parr-Brownlie and Hyland, 2005).…”
Section: Dopamine D2r Bidirectionally Modulate Schaffer Collaterals-ca1 Synaptic Plasticitysupporting
confidence: 87%
See 1 more Smart Citation
“…Our results in the episodic-like task and the cumulative semantic-like paradigm both showed that the rats performed worse in recognizing novel features of the objects in the presence of the D2R antagonist, compared to controls, during the final test sessions. These findings in rats align with reports from behavioral studies in mice in which D2R were either knocked-out or silenced specifically in the CA1 region, which demonstrated that spatial working memory (Glickstein et al, 2002), spatial and recognition learning and memory (Rocchetti et al, 2015), reversal learning and even associative learning, such as in trace eyeblink conditioning (Espadas et al, 2021) are all impaired when D2R function is disrupted. Others have reported that D2R-antagonism can affect movement initiation and execution (Amalric et al, 1993;Hauber, 1996;Parr-Brownlie and Hyland, 2005).…”
Section: Dopamine D2r Bidirectionally Modulate Schaffer Collaterals-ca1 Synaptic Plasticitysupporting
confidence: 87%
“…However, it has been reported that these receptors are not required for mossy fiber LTP or LTD in the CA3 region in vivo (Hagena and Manahan-Vaughan, 2016 ), whereas in the dentate gyrus (DG), receptor antagonism prevents weak but not strong forms of LTP in behaving rats (Manahan-Vaughan and Kulla, 2003 ). Mice lacking D2R also show reduced LTP (Espadas et al, 2021 ). D2R activation in the hippocampus has been reported to lower excitability levels and, thus, raises the threshold for induction of LTP (Manahan-Vaughan and Kulla, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, submitted work from our lab examining immediate early gene activity in neophobic and non-neophobic birds demonstrates that both phenotypes show a similar increase in neuronal activity in the AMV response to novel objects compared to non-object controls [79]. Intriguingly, some of the most highly differentially expressed genes between neophobic and non-neophobic individuals include important known neuroendocrine mediators of learning, memory, executive function, and anxiety behavior, including serotonin receptor 5A, dopamine receptors 1, 2 and 5, and estrogen receptor beta [80][81][82][83][84]. Behavioral variation has been associated with differential receptor density and gene expression in specific neuromodulatory systems in several species.…”
Section: Discussionmentioning
confidence: 99%
“…These neurons control the late stages of novel object recognition (NOR) memory by facilitating learning-induced long-term potentiation (LTP) [36]. The dopaminergic system participates in memory consolidation [37], and particularly, in the coding of novel experiences [38]. Intriguingly, the study of these neurons also suggests that there is a dopaminergic regulation that underlies cannabinergic signaling and memory consolidation.…”
Section: Canonical Action: Gabaergic Transmissionmentioning
confidence: 99%